Anesthesia management in dystrophic epidermolysis bullosa: A case report - Tetiker, Sibel; Alpay, Nilgün (Journal of Surgery and Medicine, 2021)
Epidermolysis bullosa (EB) is a rare hereditary disorder characterized by an abnormal increase in the fragility of the skin and mucosal surface and recurrent blistering. Blisters and scar formation can be seen in tissues even after a minor trauma. Due to the healing of this disease by leaving a contracted scar tissue, the findings, especially on the airway, may cause important anesthetic problems. In addition, the protection of the skin and the mucosa during the procedures to be performed, prevention of new bulla formation and prevention of infection constitute the main difficulty in anesthesia management. This case report describes the anesthesia management for the dental treatment of a patient diagnosed with dystrophic epidermolysis bullosa (DEB) and aims to review the current information.